KEBIJAKAN SISTEM PENILAIAN PRESTASI KERJA, MOTIVASI DAN KEPUASAN KERJA YANG BERIMPLIKASI TERHADAP KINERJA KARYAWAN DI PT. BANK BPD BALI KANTOR CABANG MANGUPURA - Ni Putu Anggelina (Jurnal Manajemen dan Bisnis, 2014)
The aims of this study are to analyze the effect of performance appraisal system,motivation and job satisfaction toward to performance at PT. Bank BPD Bali branches ofMangupura. This study was taken because there are still differences between the researchstudies with each other. This research was conducted using primary and secondary data.Variables used in this study were, Performance as the dependent variable and Performanceappraisal system, Motivation and Job satisfaction as an independent variables.The analysis method used is multiple linear regression analysis, previously performedclassical assumptions test that included normality test, multicollinearity test, heteroscedasticitytest, and autocorrelation test. And then the latter using multiple correlation analysis,determination analysis, t-test and F-test for hypothesis testing.The results of this study showed that, partially Performance appraisal system,Motivation and Job satisfaction has significant effect on Performance at PT. Bank BPD Balibranches of Mangupura. While, Performance appraisal system, Motivation and Jobsatisfaction are simultaneously had significant effect on Performance at PT. Bank BPD Balibranches of Mangupura. Prediction capability from these three variables toward Performanceis 98.20%, where the balance 1.80% is affected to other factor which was not to be entered toresearch model.Keywords: Performance appraisal system, Motivation, Job satisfaction and Performance